Pengaruh Subsidi Pupuk Terhadap Kesejahteraan Petani di Nagari Toboh Gadang Barat Kabupaten Padang Pariaman - Rahmanda Suci, Nesha; Widianita, Rika (STAIN Bengkalis, 2023)
The agricultural sector in Indonesia has a strategic role in the national economy, and the fertilizer subsidy policy is one of the government's efforts to improve the welfare of farmers. This study aims to analyze the effect of fertilizer subsidies on the welfare of farmers in Nagari Toboh Gadang Barat, Padang Pariaman Regency. Although fertilizer subsidies are expected to lower production costs and increase agricultural yields, research results show that the policy has not had a significant impact. Some of the problems found include uneven distribution of fertilizers, poor fertilizer quality, and dependence on external factors such as weather that affect agricultural yields. In addition, the discrepancy between the allocation of subsidies and the real needs of farmers is also a major obstacle. This study uses a quantitative method with regression analysis to test the effect of fertilizer subsidies on farmers' welfare. The results of the study show that despite the increase in agricultural output in 2023, overall agricultural productivity is still volatile and has not reached its maximum potential. Therefore, fertilizer subsidy policies need to be evaluated and improved, especially in terms of more equitable distribution, improving fertilizer quality, and adjusting subsidy allocation to the real needs of farmers. This study provides recommendations for improving fertilizer subsidy policies to be more targeted and can improve the welfare of farmers in Nagari Toboh Gadang Barat.